Urban infrastructure governance in Namibia – A multi-level analysis of urban system transitions - Savela, Nina (fi=Turun yliopisto|en=University of Turku|, 2017)
The research in this thesis was conducted as a part of the project NAMURBAN (Urban Resource Efficiency in Developing Countries – a pilot study of Walvis Bay, Namibia), a two-year project of Satakunta University of Applied Sciences in Finland. It focuses on the challenges rapid urban development imposes in Namibia and the city of Walvis Bay, on urban infrastructure governance and sectors of water, sanitation and energy. It models these sectors in forms of systems and adapts the multi-level perspective (MLP) and transition management (TM) approaches. The systems and their interactions are described in three levels: 1) the landscape level, 2) regime level and 3) technological niche level and situated in a transition model. The thesis describes the regime membership network of these regimes, the capacities of members and their perceptions towards sustainability transitions of the urban systems through adaptive capacity framework. It adapts the critical viewpoint of political ecology and other theories of political science to deepen the theoretical frameworks of transitions and adaptive capacity. The methodology of the thesis is grounded on a case study and qualitative field research, especially on participant observation method. Most of the material was received during a three-month field visit to Namibia in autumn 2016. This material includes interviews with relevant stakeholders and experts, informal discussions, literature and a questionnaire posed to external experts of the most influential forces in urban development in Namibia. As a result, the following themes are considered as the most influential forces in urban development: 1) water crisis, 2) land ownership and housing, and 3) structural deficits. Other considerable responses included urban spatial planning, public transportation and economic and social issues. The urban water and sanitation regime is characterized by an unequal distribution of water resources, outdated legislation, various practices between the regime members, varying perceptions of the need and expense of technology and the lack of public domains for discussion, key monitoring institutions and a skilled workforce. The urban energy regime is characterized by a high dependency on imported electricity, ideological division between gas and full renewable energies as means of modern electricity supply, active public debate on renewable energy solutions, the roles of independent power producers (IPPs) and market-dominating state parastatal NamPower, and the shift from a single-buyer model to a modified single-buyer model. The thesis concludes that understanding the water-energy nexus is essential in urban development; the MLP approach would highly benefit from the theoretical field of political science and should be orientated towards a developing country context. As a result, system modeling may further assist in capacity building in urban sectors.